Problems of Media Literacy Related to Medicines, Medical Products and Services - Світлана Борисівна Фіялка (Технологія і техніка друкарства, 2018)
The cases of violation of the legislation on advertising of medical products, medical products, methods of prevention, diagnostics, treatment, rehabilitation were investigated. Recommendations are given on how patients without medical education can identify ways of misleading them by representatives of medical business. There has been a problem with the advertising of drugs with unproven efficacy that do not actually have any therapeutic effect, and there are recommendations on how to use medication to check the effectiveness of drugs. Areas of critical analysis of information on means and methods of diagnostics and treatment that patients receive from physicians are offered. The biggest problem with the advertising of drugs, medical products and services is the deliberate manipulation of information. Such advertising prompts Ukrainians for self-treatment, which can lead to complications. In the Law of Ukraine ‘On Advertising’ there are very strict restrictions on medical advertising, but these are often neglected, cases of abuse are rather a rule than an exception. In our opinion, the advertising of medicines, medical goods and services should be dosed and balanced, it is necessary to involve the consultants — doctors, psychologists, who will tell how information of this or that group of people will be perceived in the process of its preparation. That is, the principle of ‘no harm’ should apply not only to drugs, medical goods and services offered in advertising, but also to the form of submission of this information. In addition, government social information campaigns are needed for people without medical education to encourage people to abandon self-treatment; to overcome ignorance, superstition and trust in obsolete and scientifically unreasonable and sometimes life-threatening treatments; to form the ability to distinguish the manipulative effect of medical advertising.